Mapping soil constraints for coconut using RS and GIS for the major coconut growing region of Tamil Nadu - Selvamani, V; Duraisami, V P (Journal of Plantation Crops, 2018)
A study was conducted to generate soil constraint maps for coconut using RS and GIS techniques. The study area covered Coimbatore and Tiruppur districts of Tamil Nadu state. A survey was conducted to collect soil samples and other basic data from 110 coconut plantations. Relationships of yield to soil properties were studied through correlation coefficient. Highest, positive and significant correlation was observed between soil depth and coconut yield. Among the physical properties studied viz., clay, silt, sand, bulk density, particle density and porespace, significant and negative correlation was obtained between sand content and yield. Based on these strong correlations, the constraints of soil parameters like soil depth, drainage, soil reaction and soil texture of the soil series were mapped for the coconut land cover of this study area. Under soil series wise constraints mapping, 3.9, 64.4 and 31.5 per cent of the total coconut land cover was found to be moderately suitable, marginally suitable and not suitable class respectively based on the most limiting constraint of the studied soil properties.